Peran Game Online dalam Perkembangan Literasi Membaca dan Akademik Remaja: Tinjauan Literatur - Rubiyanta Rubiyanta; Hanifah Ihsaniyati; Aris Widiyanto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid advancement of digital technology has made online gaming a dominant practice in the lives of adolescents, which is a topic of continued academic debate about its implications for literacy and academic achievement. The study aimed to provide a comprehensive review of the relationship between online gaming and reading literacy, including digital and printed forms, as well as academic performance among adolescents based on empirical research findings. The study used an integrative literature review methodology by conducting a systematic search of six international academic databases: Scopus, Web of Science, ScienceDirect, ERIC, MDPI, and Google Scholar. The literature review process progressed through a series of systematic stages of identification, screening, eligibility assessment, and inclusion. The review identified six empirical research studies that met the inclusion criteria. The analysis of the literature revealed a complex and multidimensional relationship between online gaming and literacy and academic achievement among adolescents. Excessive and addictive gaming behavior is also invariably linked with poor academic outcomes in terms of academic achievement and academic motivation. On the contrary, moderate levels of exposure to interactive digital environments through online gaming can contribute to the development of digital reading literacy. Moreover, various psychological and environmental factors, such as emotional regulation and literacy environment, also have a moderating role in this regard. All this emphasizes the importance of considering online gaming as part of a broader digital literacy environment in adolescents’ lives.